In vitro FORMATION OF AN ACTIVE MULTIENZYME COMPLEX IN THE TRYPTOPHAN PATHWAY OF Neurospora crassa - Arroyo-Begovich, Angel (1969)
A multienzyme complex that catalyzes the anthranilate synthetase, phosphoribosylanthranilate (PRA) isomerase, and indoleglycerolphosphate (InGP) synthetase reactions was produced in vitro when extracts from a tryp-1 mutant and a tryp-2 mutant of Neurospora crassa were mixed. The sedimentation values and the molecular weights for the interacting components obtained from the mutants were estimated by sucrose gradients and by gel filtration on Sephadex columns. The component coded for by the tryp-2 gene (a-component) which is present in the tryp-1-17 mutant has a sedimentation coefficient of 4.5S and molecular weight of 70,000. The component coded for by the tryp-1 gene (i-component) which is present in the tryp-2-6 mutant has a sedimentation coefficient 7.5S and a molecular weight of 170,000. The complex formed in vitro had similar properties to those previously reported for the wild-type complex. A Q(10) value of 3 and an apparent activation energy of 18,000 cal/mole were calculated for the formation of the complex from the two components.